2015
DOI: 10.4102/ajlm.v4i1.158
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterisation of multidrug-resistant <i>Salmonella enterica</i> serotypes isolated from poultry in Cairo, Egypt

Abstract: Background: Food-borne diseases pose serious health problems, affecting public health and economic development worldwide.Methods: Salmonella was isolated from samples of chicken parts, skin samples of whole chicken carcasses, raw egg yolks, eggshells and chicken faeces. Resulting isolates were characterised by serogrouping, serotyping, antimicrobial susceptibility testing and detection of extended-spectrum β-lactamase (ESBL) production. Antibiotic resistance genes and integrons were identified by polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
2
25
3
4
Order By: Relevance
“…As is shown in Table , multi drug resistance was seen in isolates. Detected antibiotic resistance to nalidixic acid (Quinolones) and erythromycin (macrolid) was reported in other findings for Salmonella isolates (Abdel‐Maksoud et al, ; Braoudaki & Hilton, ; Musgrove et al, ; Thung et al, ). It is notable, as quinolones are the last options against the multidrug resistant drugs salmonella isolates (Abdel‐Maksoud et al, ).…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…As is shown in Table , multi drug resistance was seen in isolates. Detected antibiotic resistance to nalidixic acid (Quinolones) and erythromycin (macrolid) was reported in other findings for Salmonella isolates (Abdel‐Maksoud et al, ; Braoudaki & Hilton, ; Musgrove et al, ; Thung et al, ). It is notable, as quinolones are the last options against the multidrug resistant drugs salmonella isolates (Abdel‐Maksoud et al, ).…”
Section: Resultsmentioning
confidence: 55%
“…As is shown in Braoudaki & Hilton, 2005;Musgrove et al, 2006;Thung et al, 2016). It is notable, as quinolones are the last options against the multidrug resistant drugs salmonella isolates (Abdel-Maksoud et al, 2015). Improper, overdose, and worldwide use of antibiotics in human and veterinary medicine are the main reasons of antibiotic resistance due to genetic adaptations of microorganisms and presence of integrons as genetic elements with the ability of identifying and capturing carriers of antibiotic resistance genes (mobile gene cassettes) which cause multi drug resistance (Abdel-Maksoud et al, 2015;Aguilar-Montes et al, 2017).…”
Section: Antibiotic Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Fluoroquinolones have actually been considered as one of the last options for the treatment of Salmonella spp. (Abdel-Maksoud et al, 2015). The absence of the qnr-A gene in isolates that had a positive phenotype indicated that the disc diffusion method may either be more sensitive and causing a few false positive.…”
Section: Discussionmentioning
confidence: 99%